The role of volunteering in the development of tourism (Journal of Geography and Environmental Management, 2017)
Volunteering plays an important role in the development of society and the solution of socio-economic, cultural and environmental problems. The organization of leisure with the help of volunteerism, which today is considered as a trend, is one of the rapidly developing directions of the tourism industry. Volunteering enables tourists to expand their knowledge about self-development, about their own country, history, culture, traditions of other countries, to be attentive to the world around, to test themselves in new conditions. Thus, volunteers, taking part in solving international, regional, local social problems, have the opportunity to organize their vacation in a combination of «useful and enjoyable.»The article considers theoretical and methodological foundations of volunteering, analyzes statistical data on the development of volunteerism in the world. Also, various points of view of domestic, Russian and foreign scientists on the concept of «volunteer» are presented, an analysis of the terminology existing today is given. At the same time, the relationship between volunteerism and tourism, and such concepts as «volunteer performance» and «volunteerism» is revealed. The article contains examples of existing international volunteer programs, their activities, reveals the role of volunteerism in the development of tourism.